Reinterpreting Husband's Obligations in the Tabligh Jama'ah Pontianak: Analytical Study of Article 80 Compilation of Islamic Law (Program Studi Hukum Keluarga Islam, 2025)
The study aims to determine how the Jama’ah Tabligh Pontianak (Pontianak’s Tabligh/ da’wah congregation) interprets the obligations of husbands in Article 80 of the KHI (Compilation of Islamic Law) and how this interpretation may differ from the normative legal perspective. According to the Pontianak Tabligh congregation, as a husband, the obligation to provide religious education to his wife is more important than other obligations, even though the Marriage Law and the Compilation of Islamic Law do not state this. This is classified as normative research with a legal and theoretical approach. Data was obtained through in-depth interviews. Informants were determined through purposive sampling. The results of the study show that the Pontianak Tabligh congregation's interpretation of a husband's obligations emphasises the spiritual and cognitive dimensions of a husband's responsibilities. This perspective shows a shift in the meaning of obligations from material aspects to moral-transcendental aspects. The interpretation is based on the principle that every Muslim has an obligation to seek religious knowledge and the understanding that a wife is the first school for her children. The Pontianak Tabligh congregation establishes a hierarchy of the obligations for husbands, ranking the obligation to provide religious education first and permanently. Normatively, this view needs to be aligned with the principles of positive law to avoid biased interpretations of the law, because in responsive legal theory, a rule must be responsive to social dynamics. This study provides a new perspective on the obligations of husbands and offers input for religious institutions and the government on how to respond to the dynamics of legal understanding in society, especially in the field of Islamic marriage law.